Konen: Sebuah Ritual Doa kepada Leluhur - Yohanis Kristianus Tampani; Augusta De Jesus Magalhaes (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
Konen is a ritual prayer to ancestors practiced by the community in Numponi Village, East Malaka District, Malaka Regency. This qualitative research uses observation, interviews, and literature study. The findings reveal three key aspects. First, the word konen derives from onen in the Dawan language, meaning “prayer.” It is a traditional ceremony led by the tribal chief to request guidance, blessings, and protection from ancestral spirits through God. Rituals vary depending on the occasion—such as corn harvest, marriage, or migration. Second, the konen ritual takes place in a traditional house with offerings including a rooster, betel nut, areca nut, and candles. The rooster is sacrificed as an offering to ancestors in gratitude. Third, the symbolic meaning of konen lies in the offerings, which represent gratitude and serve as a spiritual link between the living and ancestral spirits. These symbols are believed to summon ancestral spirits who may grant the requests presented during the ritual. Konen is a cultural expression of faith, gratitude, and connection to ancestral heritage, reinforcing the tribe’s cultural and spiritual identity.